Geography and geographical knowledge contribute decisively to all sustainable development goals and targets - Paulo Pereira; Wenwu Zhao (Geography and Sustainability)
Geography is a discipline that touches multiple sciences and has been key to bridging numerous fields of knowledge. This gives geography the advantage of connecting natural (e.g., biology, ecology, climatology, geomorphology) with social and human (e.g., education, demography, sociology) sciences. The spatialisation of information from different sciences allows us to understand distribution patterns and connections between different realities. Thus, geographical knowledge is essential for an integrated and consistent understanding of our world. The Sustainable Development Goals (SDGs) established by the United Nations (UN) in 2015 were essential to unifying the world towards a common goal. To achieve these, 17 goals and 169 targets were created, and knowledge from multiple sciences is needed to support them. It is a huge challenge, and different knowledge branches are needed to connect. Geography and geographical knowledge have this capacity and support all 17 goals and 169 targets. Although this is a reality, as it will be explained in this editorial, SDG’s achievement for some is becoming utopic and unrealistic due to our world’s differences. It is time to think about the post-2030 SDGs, in which geography and geographic knowledge will be essential unequivocally.